DISCOURSE STRATEGY IN THE GREAT DEBATERS FILM DIALOGUE (Critical Discourse Analysis) - Tomson Sabungan Silalahi; Zainal Rafli; Ratna Dewanti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT Knowledge, attitudes, values, norms or ideology are all personal representations and social representations. Each text will never be separated from personal and social representation. Using Critical Discourse Analysis, this article aims to reveal the discourse strategies used by the dialogue writers of the film The Great Debaters. To elaborate, the writer will use several steps, namely analyzing the macro structure, micro structure including the Description of Actors and Events and Interpretation of Racism Discourse in the United States. Based on the overall strategy of composing the dialogue text it can be concluded that Harpo Production is not neutral. Discourse compilation strategy is applied consciously by the parties involved in the scenario processing. It was found that the discourse strategy reflected the alignment of certain discourse stakeholders, namely the African-American community. Keywords: Critical Discourse Analysis, Dialog, Film, Discourse Strategy